− 174 G>C IL-6 polymorphism and primary iron overload in male patients - Tetzlaff, Walter F. (2018)
Primary iron overload (IO) is commonly associated with mutations in the hereditary hemochromatosis gene (HFE). Nonetheless, other genetic variants may influence the development of IO beyond HFE mutations. There is a single nucleotide polymorphism (SNP) at − 174 G>C of the interleukin (IL)-6 gene which might be associated with primary IO. Our aim was to study the association between the SNP − 174 G>C gene promoter of IL-6 and primary IO in middle-aged male patients. We studied 37 men with primary IO diagnosed by liver histology. Controls were age-matched male volunteers (n = 37). HFE mutations and the SNP − 174 G>C gene promoter of IL-6 were evaluated by PCR-RFLP. Logistic regression was used to evaluate the association between primary IO and SNP − 174 G>C gene promoter of IL-6. Patients and control subjects were in Hardy-Weinberg equilibrium for the SNP − 174 G>C gene promoter of IL-6 (p = 0.17). Significantly different genotype frequencies were observed between patients (43% CC, 43% CG, and 14% GG) and control subjects (10% CC, 41% CG, and 49% GG) (OR = 4.09, 95% CI = 2.06–8.13; p < 0.0001). The multiple logistic regression analysis showed that IO was significantly associated with CC homozygosis in the SNP − 174 G>C gene promoter of IL-6 (OR = 6.3, 95% CI = 1.9–21.4; p < 0.005) in a model adjusted by age and body mass index. In conclusion, CC homozygosis in the SNP − 174 G>C gene promoter of IL-6 can be proposed as one of the gene variants influencing iron accumulation in male adults with HFE mutations. Studies in larger cohorts are warranted.